MATERIALS ON HELMINTH FAUNA IN GRASS FROGS RANA TEMPORARIA LINNAEUS, 1768 (AMPHIBIA: ANURA) IN THE REPUBLIC OF MORDOVIA - I. V. Chihlyaev; A. B. Ruchin (Российский паразитологический журнал, 2016)
The records of helminth fauna from grass frogs Rana temporaria Linnaeus, 1768 of Republic of Mordovia are provided. 16 helminth types have been discovered: 1 – Monogenea, 11 – Trematoda, and 4 – Nematoda. Dominating in quantity of types the adult and larval trematodes are characterized by a lower infeсtion rate and beong to rare parasites of the specific host. Geonematodes Rhabdias bufonis (Schrank, 1788) and Oswaldocruzia filiformis (Goeze, 1782) are background parasites with a high infection rate found in all frogs; nematodes Cosmocerca ornata (Dujardin, 1845), trematodes Haplometra cylindracea Zeder, 1800 and Pleuro-genes claviger (Rudolphi, 1819) occur more rarely. The differences of single amphibian populations are determined based on various structures of trematodes and depend on biotopical conditions.